Correlates of Farmers' Knowledge of Recommended Water Productivity Practices - Hiwarkar, G. R. , P. K. Wakle , A. S. Gomase and Lambe, S. P., (Indian Journal of Extension Education, 2014)
The study was carried out in Buldana and Yavatmal district in Maharashtra state to know the farmers' knowledge aboutrecommended Water Productivity practices. Krishi Vigyan Kendra, Buldana and Yavatmal were selected purposively asthese KVKs have organized trainings on water productivity practices. From each KVK , 25 respondents who attended thetrainings were selected randomly. Thus a total 50 respondents were personally contacted for data collection. The studyrevealed that more than half respondents possessed moderate knowledge about recommended practices of waterproductivity practices. The relational analysis showed that education qualification, risk reference, sources of information,sources of irrigation and innovativeness were positively correlated with the extent of knowledge of recommended waterproductivity practices by the respondents.